(untitled) (Journal of the College of Basic Education, 2022)
The current research aims to develop the rhetorical skills of public speaking and diction for students of the College of Fine Arts, University of Diyala, where the research problem was identified by the weakness of the rhetoric skills of the students. After the application of the program, the appropriate statistical methods were used, and it was concluded that there is a significant impact of the training program in developing verbal skills, and accordingly it recommended its adoption